PRONUNCIATION VARIABILITY OF ENGLISH DENTAL FRICATIVES AMONG SUNDANESE LEARNERS IN DIFFERENT ACADEMIC DISCIPLINES - Awwali, Jasmine Nadira; Indrayani, Lia Maulia; Amalia, Rosaria Mita (English Review: Journal of English Education, 2024)
Clear pronunciation is a critical component of successful communication, essential for developing both speaking and listening skills. However, pronunciation challenges often arise due to differences between written and spoken forms of a language, as well as the influence of a speaker's native language. This study examines the production of English dental fricative consonant sounds by Sundanese students from English and non-English departments at Widyatama University, Indonesia. The study aims to identify common pronunciation errors and their causes, comparing students who have extensive English training with those who do not. A qualitative descriptive method was employed, supported by content analysis, to analyze the pronunciation of 10 students—five from each department. The findings reveal significant differences in pronunciation accuracy between the two groups, with English Department students generally performing better. Common errors include the substitution of dental fricatives with alveolar stops and labiodental fricatives with bilabial plosives. The primary causes of these errors are attributed to insufficient practice, lack of phonetic awareness, and interference from the native Sundanese language. This research highlights the need for targeted pronunciation training and increased phonetic awareness to improve English pronunciation skills among non-English majors.